Comparative proteomic analysis of round and elongated spermatids during spermiogenesis in mice. (5th February 2020) - Li, Meining; Li, Huahua; Yang, Hong; Cheng, Rina; Zheng, Pengdou; Guo, Rui
Abstract: Spermiogenesis in mammals is an exclusive process during which haploid round spermatids mature into spermatozoa in the testis. Any abnormality in the process of spermiogenesis may result in male infertility. The aim of the present study was to characterize the differentially expressed proteins between round and elongated spermatids in mice using label‐free quantitative mass spectrometry. Of the 2411 proteins identified in this study, 333 were differentially expressed with a ≥10‐fold change, including 208 upregulated proteins and 125 downregulated proteins in round spermatids relative to elongated spermatids. Gene Ontology analysis showed that these differentially expressed proteins were categorized into 10 types of subcellular localizations, 9 molecular functions, and were involved in 9 biological processes. All the identified proteins participated in 268 different pathways. In addition, ubiquitin‐mediated proteolysis and the proteasome pathway, autophagy, lysosome, and apoptosis pathways were involved in the mechanism of spermiogenesis. Our data may provide valuable information for a better understanding of spermiogenesis and help improve the diagnosis and treatment of male factor infertility.